No transit timing variations in WASP-4 - Petrucci, Romina Paola (2013)
We present six new transits of the system WASP-4. Together with 28 light curves published in the literature, we perform a homogeneous study of its parameters and search for variations in the transits´ central times. The final values agree with those previously reported, except for a slightly lower inclination. We find no significant long-term variations in i or RP/Rsol. The O-C mid-transit times do not show signs of transit timing variations greater than 54 s.